2017
DOI: 10.1161/strokeaha.116.014988
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation Potentiates Improvements in Functional Ability in Patients With Chronic Stroke Receiving Constraint-Induced Movement Therapy

Abstract: URL: http://www.clinicaltrials.gov. Unique identifier: NCT01983319.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 11 publications
0
33
2
4
Order By: Relevance
“…Studies in the area of rehabilitation have indicated that continuous tDCS improved motor function (Costa-Ribeiro et al, 2016; Ilić et al, 2016; Yozbatiran et al, 2016; Figlewski et al, 2017). Thus, continuous tDCS is likely to affect an individual’s AQ score.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the area of rehabilitation have indicated that continuous tDCS improved motor function (Costa-Ribeiro et al, 2016; Ilić et al, 2016; Yozbatiran et al, 2016; Figlewski et al, 2017). Thus, continuous tDCS is likely to affect an individual’s AQ score.…”
Section: Discussionmentioning
confidence: 99%
“…She was treated with IV thrombolysis and thrombectomy and recanalization was achieved 5 h after symptom onset. One year post-stroke she still suffered from motor impairment (Wolf Motor Function Test [WMFT] score of 30) and was scanned as part of a clinical study investigating the effect of combining Constraint-Induced Movement Therapy and tDCS (Figlewski et al, 2017; Clinical trials NCT01983319, Regional Ethics approval: 1-10-72-268-13). The structural scans showed a cortical lesion in the right parietal lobe (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Six studies involving eight used a bilateral montage, including the anodal stimulation of M1 of the ipsilesional hemisphere (C3 and C4 EEG 10/20 system), cathodal stimulation of M1 of the controlesional hemisphere or cathodal stimulation of the contralateral supraorbital area to the lesion [12][13][14][15][16][17][18][19]. Bilateral montage is often used based on the assumption that the movements of the impaired limbs are often associated with a high level of transcallosal inhibition by the hemisphere not affected by the hemisphere being injured [10,20]; some studies conducted with multimodal imaging techniques and mapping, such as fMRIs and TMSs, confirmed the existence of this imbalance of the hemisphere not affected, also called a hemispheric competition model, particularly during the preparation and execution of upperlimb motor acts [21,22], some authors hypothesize that the amount of this imbalance in inter-hemispheric excitability may be positively correlated with the degree of severity of motor disability [10,6].…”
Section: Discussionmentioning
confidence: 99%
“…Five out of eight studies contributed to the administration of tDCS to the rehabilitation treatment, reporting a significant increase compared to the control groups [12,13,16,17]; Straudi et al using Upper Extremity Robot-Assisted Training however showed a general improvement in motor function in both groups, and the lack of significant superiority between the experimental group and the control group. It has been hypothesized that peripheral training, meant as functional motor tasks designed to promote sensorimotor integration, coordination of movements and goal-directed activities of practical relevance [12], in combination with tDCS could improve the acquisition of motor skills and the respective consolidation of the same through a mechanism LTD due to the increase in inputs versus the cortex while its intrinsic excitability is modified by tDCS [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation